(untitled) (Journal of Hama University, 2024)
The aim of the current research is to analyze the content of the science book for the fifth basic grade to investigate the degree of availability of some higher-order thinking skills. The researcher adopted the content analysis method from the descriptive approach. The sample of the research was the science book for the fifth basic grade, which contains four units, and the curriculum is for the fifth basic grade of The Syrian Ministry of Education for the academic year 2018/2019, and the research tool was an analysis card, based on a list prepared by the researcher that included four skills: (organization - data analysis and modeling - open-ended problem solving - application). The researcher found that the skill most frequently found in the science textbook for the fifth grade is the skill of organization, at (36.79%), with a high degree, then the solving open ended problems skill, at (24.87%), followed by the analyzing and modeling data skill, at (22.28%), with a middle degree for both skills, then the application skill came in fourth and last place, at (16.06%), with a low degree. Based on these results, the researcher presented several proposals, the most important of which are: developing teachers’ competencies to apply higher-order thinking skills, and designing enrichment programs and activities to develop higher-order thinking skills among learners.